A TALE OF THE UNEXPECTED: ISOLATED FRONTAL LOBE AMYLOIDOMA. Issue 10 (9th September 2014) - Pace, Adrian; Shivane, Aditya; Hilton, David; Weatherby, Stuart
Abstract : Amyloidosis is a heterogeneous group of diseases that may take on many forms and involve different organ systems. Within the brain, it most commonly manifests as amyloid angiopathy or senile plaques. We present a case of isolated cerebral amyloidoma with no evidence of systemic involvement. A 48 year old woman presented to hospital in convulsive status epilepticus. Her medical history was significant for anorexia nervosa and bipolar disorder. Baseline serology and toxicology were normal. Head computed tomography (CT) showed a non-enhancing, calcified, paramedian, left frontal lobe lesion. The lesion was hypointense on T2-weighted magnetic resonance imaging and isointense on T1-weighted imaging, enhancing intensely with gadolinium. Body CT did not reveal a neoplastic primary. The lesion was completely resected. Microscopic examination of the excised tissue revealed large deposits of amorphous acellular eosinophilic material confirmed to be amyloid by special stains. The brain parenchyma also showed moderate lymphoplasmacytic infiltrate comprising a clonal population of B cells with λ-light chain restriction. Bone marrow biopsy and SAP scans were normal. There was no paraproteinaemia or haematological abnormality. Serial imaging since has not shown recurrence, and the patient remains seizure-free. Cerebral amyloidoma should be part of the differential diagnosis of a solitary cerebral mass, as its favourable clinical course compared to intracerebral neoplasm or metastasis significantly alters long-term prognosis.